Cytoreductive surgery followed by chemotherapy and olaparib maintenance in BRCA 1/2 mutated recurrent ovarian cancer: a retrospective MITO group study. Issue 7 (14th May 2021) - Cecere, Sabrina Chiara; Musacchio, Lucia; Bartoletti, Michele; Salutari, Vanda; Arenare, Laura; Lorusso, Domenica; Ronzino, Graziana; Lauria, Rossella; Cormio, Gennaro; Naglieri, Emanuele; Scollo, Paolo; Marchetti, Claudia; et al.
Abstract : Introduction: The role of cytoreductive surgery in the poly-ADP ribose polymerase inhibitors era is not fully investigated. We evaluated the impact of surgery performed prior to platinum-based chemotherapy followed by olaparib maintenance in platinum-sensitive BRCA-mutated recurrent ovarian cancer. Methods: This retrospective study included platinum-sensitive recurrent ovarian cancer BRCA-mutated patients from 13 Multicenter Italian Trials in Ovarian cancer and gynecological malignancies centers treated between September 2015 and May 2019. The primary outcomes were progression-free survival and overall survival. Data on post-progression treatment was also assessed. Results: Among 209 patients, 72 patients (34.5%) underwent cytoreductive surgery followed by platinum-based chemotherapy and olaparib maintenance, while 137 patients (65.5%) underwent chemotherapy treatment alone. After a median follow-up of 37.3 months (95% CI: 33.4 to 40.8), median progression-free survival in the surgery group was not reached, compared with 11 months in patients receiving chemotherapy alone (P<0.001). Median overall survival was nearly double in patients undergoing surgery before chemotherapy (55 vs 28 months, P<0.001). Post-progression therapy was assessed in 127 patients: response rate to chemotherapy was 29.2%, 8.8%, and 9.0% in patients with platinum-free interval >12 months, between 6 and 12 months, and <6 months, respectively. Conclusion: Cytoreductive surgery performed before platinum therapy and olaparib maintenance was associated with longer progression-free survival and overall survival in BRCA-mutated platinum-sensitive relapsed ovarian cancer patients. In accordance with our preliminary results, the response rate to chemotherapy given after progression during olaparib was associated with platinum-free interval.